"I used to be a traitor": Russian Baptist Conversion as Unlearning - Mikeshin, Igor (Approaching religion, 2024)
This article discusses adult conversion in the Russian Baptist community as the unlearning of old sinful ways of living. Russian Baptists see conversion as an act of repentance, surrendering to Christ, and becoming born again, and as a life-long process of growing in faith. Based on an ethnographic study of the Baptist community in north-western and central Russia, the article discusses the glocal nature of the Russian Baptist community that attracts the kind of people that convert to this faith and the circumstances of their conversion. Russian Baptist conversion is viewed as an act and a process, and conversion is seen as an ethical choice and an unlearning of the old ways of living.